KARAKTERISTIK TIM YANG EFEKTIF UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH - Istanto; Murjani; Arbainsyah; Ahmad Yani; Nur Nida Karimah (al-Afkar, Journal For Islamic Studies, 2022)
EFFECTIVE TEAM CHARACTERISTICS FOR IMPROVING THE QUALITY OF EDUCATION IN SCHOOL This paper aims to explore the basic characteristics of teams and the effectiveness of team characteristics in improving the quality of education in schools. Characteristics of an effective team to improve the quality of education in schools are high participating teams, open communication, clarity of roles and work assignments. The process of team work in schools is directed at achieving school goals that are in line with the vision and mission. As educational service institutions, schools are expected to be able to use all available resources effectively to achieve their goals and use resources efficiently. A cohesive or cohesive team is important, team cohesiveness means the extent to which group members are attracted to each other and feel part of the group. The higher the power of synergy between members and leaders, the higher the strength of a team. The principal and the entire school community play a major role in carrying out the pattern of school management, both collectively and individually.